An ecofriendly phosphorylation of wool using Maillard reaction for improving cationic dye absorption. (20th March 2018) - Cui, Li; Yuan, Jiugang; Wang, Ping; Wang, Xingping; Fan, Xuerong; Wang, Qiang
Abstract: Phosphorylated wool with enhanced ability to absorb cationic dyes is helpful to dye wool fabrics using cationic dyes with good dyeing properties, which is more economic and ecofriendly compared to the traditional dyeing process of acid dyes with poor wet fastness. Phosphorylation can be performed by applying chemical reagents which tend to cause a problem of environmental pollution and the fibers can be damaged seriously under harsh reaction conditions, or using enzymes which are currently somewhat discouraged due to significant cost of the enzymes and their decreased stability at the reaction conditions. In this study, non-toxic glucose 6-phosphate was applied to phosphorylated modification of wool via Maillard reaction under a mild condition to enhance the dyeing properties of wool fabric for cationic dyes. The reaction between glucose 6-phosphate and wool keratin was demonstrated from the results of sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), particle diameter, Fourier transform infrared spectra (FTIR) and Energy Dispersive X-ray test (EDS). It was found that phosphorylation modification scarcely changed the mechanical properties of the wool fabric. Maillard browning on the wool could be avoided by accurately controlling the reaction time. Dyeing properties of phosphorylated wool fabric with cationic dyes were markedly enhanced. The exhaustion of phosphorylated wool fabric for two cationic dyes: Cationic Brilliant Red 5 GN and Brilliant Yellow B 6 GL increased from 38.6% to 18.9%–84.5% and 67% respectively by comparing with that of the wool fabric without modification and better color strength (K/S) and very good wash fastness properties obtained. The results indicated that phosphorylated modification of wool with glucose 6-phosphate could be a potential, safe and cleaner approach to develop a more efficient and economic dyeing process for wool fibers with cationic dyes. Graphical abstract: Image Highlights: Wool fibers are phosphorylated through Maillard reaction under a mild condition. Maillard browning can be avoided by accurately controlling the reaction time. Phosphorylated wool fabrics are well dyed with cationic dyes.